Open the Eyes: Photography and Architecture - Martínez Arroyo, Carmen; Pemjean, Rodrigo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
“To photograph is to place the head, the eye and the heart in the same axis”. This sentence of Henri Cartier-Bresson expresses with clarity what is, for him, to photograph. First, the abstract condition of the mind. Secondly, the technique present in our eye and in the objective of the camera. And, finally, the incorporation of the heart in our work, the fact that the element photographed is able to activate our emotions. This article is in debt to the text of Cartier- Bresson and is structured in three parts, related to the head, the eye and the heart. But it is above all an excuse to reflect on how to open our eyes to the world around us. From drawing, from built reality or from photography.
Keywords: Photography; Architecture; Scale; Eye; Life